Propuesta para el diseño de un centro de interpretación turístico, ambiental y cultural para el cantón Pallatanga, provincia de Chimborazo - Estupiñan Campuzano, Karen Kimberley (2014)
The principal objective of present project is: to design a Center of Tourism, Environment and Culture, for cantón Pallatanga, province of Chimborazo. To design a market study was conducted in two cities: Pallatanga, Riobamba and students of the from Ecotourism of the UTEQ analyzing the preferences of tourists visiting the interpretive center, supply and demand surveys analyzed by ; then proceeded to conduct a technical study to design features for the construction of the center, the types of interpretive media as information panels and vases, in addition to an interpretive script with several themes revealing the full potential of Pallatanga was defined using brand runner-Cumanda Pallatanga sustainable tourism as corporate image and architectural drawings of the Interpretation Centre were developed. Meetings were held with the coach tourism and environment Pallatanga to define the organizational structure and operating functions of the Interpretation Centre and finally the economic analysis and financial evaluation, where an investment of USD 86,224.34 was determined an actual value was made net (NPV) of USD 86,217.83 internal rate of return (IRR) of 45.71%.